The Interest that students from the Modern Languages Major, Specialty in French And English, of the University of El Salvador have to meet the requirements to obtain The Teaching Scale issued by the Ministry of Education - Peña Ramos, Ángel Rodolfo; Guzmán Palacios, Jennifer Geanina; Quijano Rivas, José Saúl (2024)
This research intent to start an understanding of the interest that students have to meet the requirements to obtain the Teaching Scale issued by the Ministry of Education. The topic of the Teaching Scale becomes very important for many students who wish to dedicate themselves to the teaching field. This research shows concepts, explanations and real data taken from official sources to support this work, such as the meaningful learning theory. The information given in this work shows us important data on how the Modern Languages Major curricula is constructed, and also explores the elements and some of the requirements that graduates of the Modern Languages Major must meet in order to obtain the Teaching Scale. In addition, it covers topics of interest that have caught the attention of some students, such as how to meet the requirements and know processes that must be followed in order to obtain the Teaching Scale. In addition, part of the research that was conducted was based on a survey technique where students could show us a knowledge, opinions and ideas that they have as students. The answers obtained from the students' opinions were associated with the information presented in our theoretical framework, and by interpreting the opinions and answers of the students surveyed, we can represent a real percentage of the answers given by the population. To conclude, this research contains the data analysis of the instruments delivered to students, which are taken hand in hand with the information provided in the theoretical framework.